Budesonide/Formoterol Anti-Inflammatory Reliever and Maintenance or Fluticasone Propionate/Salmeterol Plus As-Needed, Short-Acting β2 Agonist: Real-World Effectiveness in pAtients without Optimally Controlled asThma (REACT) Study - Cheng SL (Drug Design, Development and Therapy, 2020)
Shih-Lung Cheng,1,2 Ming-Lin Ho,3 Yun-Fa Lai,4 Hao-Chien Wang,5 Jeng-Yuan Hsu,6 Shih-Feng Liu,7,8 Ming-Shyang Huang,9 Cheng-Hung Lee,10 Ching-Hsiung Lin,3,11 Liang-Wen Hang,12,13 Yu-Chih Liu,14 Kuang-Yao Yang,15,16,* Jia-Horng Wang14,17,* 1Department of Internal Medicine, Far Eastern Memorial Hospital, New Taipei City, Taiwan; 2Department of Chemical Engineering and Materials Science, Yuan-Ze University, Taoyuan, Taiwan; 3Division of Chest Medicine, Kuang Tien General Hospital, Taichung, Taiwan; 4Department of Internal Medicine, E-Da Hospital, I-Shou University, Kaohsiung, Taiwan; 5Department of Internal Medicine, National Taiwan University Hospital, Taipei, Taiwan; 6Division of Clinical Research, Taichung Veterans General Hospital, Taichung, Taiwan; 7Department of Respiratory Therapy, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 8Division of Pulmonary and Critical Care Medicine, Department of Internal Medicine, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 9Department of Internal Medicine, E-DA Cancer Hospital and Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 10Division of Chest Medicine, Department of Internal Medicine, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan; 11Division of Chest Medicine, Changhua Christian Hospital, Changhua, Taiwan; 12School of Nursing & Graduate Institute of Nursing, China Medical University, Taichung, Taiwan; 13Sleep Medicine Center, China Medical University Hospital, Taichung, Taiwan; 14Department of Internal Medicine, Keelung Chang Gung Memorial Hospital, Keelung, Taiwan; 15Department of Chest Medicine, Taipei Veterans General Hospital, Taipei, Taiwan; 16Institute of Emergency and Critical Care Medicine, School of Medicine, National Yang-Ming University, Taipei, Taiwan; 17Hyperbaric Oxygen Center, Far Eastern Memorial Hospital, New Taipei City, Taiwan*These authors contributed equally to this workCorrespondence: Kuang-Yao Yang; Jia-Horng Wang Tel +886-2-28757455Fax +886-2-28757610Email kyyang@vghtpe.gov.tw; jiahorng.wang@gmail.comIntroduction: In the prospective, observational, 16-week REACT study conducted between October 21, 2008 and May 12, 2011, we compared the real-world effectiveness of anti-inflammatory reliever and maintenance therapy with budesonide/formoterol (Symbicort® Turbuhaler) and maintenance therapy with fixed-dose fluticasone/salmeterol (Seretide®) plus as-needed, short-acting β2 agonists (SABAs) in Taiwanese patients with inadequate asthma control.Methods: Asthma control was assessed using the five-item Asthma Control Questionnaire (ACQ-5) and standardized pulmonary function testing. Assessments were performed at baseline and at weeks 4– 5 and 12– 16. Overall, we enrolled 842 patients at 11 clinics, 723 of whom were included in analyses (budesonide/formoterol, 563.3± 1.3 μg/d, n=551; fluticasone/salmeterol, 1013.8± 1.4 μg/d, n=172).Results: At baseline, 72.5% and 27.5% of all patients had “partly” and “uncontrolled” asthma, respectively. Mean±SD ACQ-5 scores were 1.54± 1.06 and 1.46± 1.28 in the budesonide/formoterol and fluticasone/salmeterol groups, respectively. ACQ-5 scores significantly improved from baseline (ie, decreased) in both groups at weeks 4 and 16. ACQ-5 difference scores were significantly lower in the budesonide/formoterol group (− 0.91± 1.11) than the fluticasone/salmeterol group (− 0.69± 1.27) at the end of the study (p=0.027). Peak expiratory flow rate significantly improved from baseline in the budesonide/formoterol but not the fluticasone/salmeterol group at the end of the study. Severe exacerbation rates and medical resource utilization were comparable between the budesonide/formoterol and fluticasone/salmeterol groups.Conclusion: Collectively, results indicate the real-world effectiveness of budesonide/formoterol anti-inflammatory reliever and maintenance therapy is better than fixed-dose fluticasone/salmeterol plus as-needed SABA.Trial Registration: ClinicalTrials.gov registration number: NCT00784953.Keywords: budesonide/formoterol, fluticasone propionate/salmeterol, anti-inflammatory reliever and maintenance, real-world